Analysis of the effect of holmium laser flexible ureteroscopic intrapelvic drainage in the treatment of parapelvic renal cysts - Yuanshen Mao; Wenfeng Li; Jun Da; Mingxi Xu; Yiwei Wang; Yufei Gu; Weixin Pan; Zhong Wang (Asian Journal of Urology)
Objective: To explore the efficacy, safety, and feasibility of holmium laser flexible ureteroscopic intrapelvic drainage in the treatment of parapelvic renal cysts. Methods: From September 2012 to February 2019, a total of 18 patients, aged from 28 to 62 (mean±standard deviation [SD]: 46.50±9.14) years, were diagnosed with parapelvic renal cysts and treated by holmium laser flexible ureteroscopic intrapelvic drainage. There were 10 males and eight females. All of the parapelvic renal cysts were unilateral, and two cases were complicated with pyelolithiasis. The diameters of the cysts ranged from 4.1 cm to 8.2 cm. Results: All the patients completed the operation successfully in one stage without conversion to open surgery; in two cases, it was difficult to find the cysts during the operation, and the localization was completed by B-ultrasound and percutaneous injection of methylene blue. The mean operative time was 33.89 (SD: 9.68; range: 22–54) min, and the mean hospitalization time was 2.67 (SD: 0.91; range: 2–5) days. Three months and 6 months of follow-up were performed after surgery. The cysts disappeared in 13 (72%) cases, and the diameter of the cysts in five (28%) cases decreased by more than 50%. Conclusion: Holmium laser flexible ureteroscopic intrapelvic drainage in the treatment of parapelvic renal cysts is simple, safe, and effective, and can be used as the first choice for the treatment of parapelvic renal cysts.